Prevalence and Prognostic Value of Mesenteric Artery Stenosis in Patients Undergoing Transcatheter Aortic Valve Implantation - Lu, Henri; Rotzinger, David; Monney, Pierre; Muller, Olivier; Egea, Michael; Grange, Matthieu; Eeckhout, Eric; Kirsch, Matthias; Qanadli, Salah D. (Frontiers in Cardiovascular Medicine, 2022)
Introduction Data regarding the prevalence of mesenteric artery stenosis in patients undergoing transcatheter aortic valve implantation (TAVI) are scarce. Whether patients with high-risk features for acute mesenteric ischemia (AMesI) have a worse prognosis compared with those without high-risk features is unknown. We aimed to address these questions. Methods We included 361 patients who underwent TAVI between 2015 and 2019. Using pre-TAVI computed tomography exams, the number of stenosed arteries in each patient and the degree of stenosis for the coeliac trunk (CTr), SMA and inferior mesenteric artery (IMA) were analyzed. High-risk features for AMesI were defined as the presence of ≥2 arteries presenting with ≥50% stenosis. Patient demographic and echocardiographic data were collected. Endpoints included 30-day all-cause mortality, mortality and morbidity related to mesenteric ischemia. Results 22.7% of patients had no arterial stenosis, while 59.3% had 1 or 2 stenosed arteries, and 18.0% presented stenoses in 3 arteries. Prevalence of significant stenosis (≥50%) in CTr, SMA, and IMA were respectively 11.9, 5.5, 10.8%. Twenty patients at high-risk for AMesI were identified: they had significantly higher all-cause mortality (15.0 vs. 1.2%, p < 0.001) and higher mortality related to AMesI (5.0 vs. 0.3%, p = 0.004), compared with non-high-risk patients. Conclusions Patients at high-risk for AMesI presented with significantly higher 30-day all-cause mortality and mortality related to AMesI following TAVI. Mesenteric revascularization before TAVI interventions may be beneficial in these patients. Prospective studies are needed to clarify these questions.